2017
DOI: 10.1039/c6cy02489k
|View full text |Cite
|
Sign up to set email alerts
|

Selective corrosion of LaCoO3 by NaOH: structural evolution and enhanced activity for benzene oxidation

Abstract: NaOH corrosion of electrospun LaCoO3 shows enhanced benzene oxidation activity due to mutual effects among La2O3, Co3O4 and LaCoO3.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
19
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 55 publications
(22 citation statements)
references
References 24 publications
3
19
0
Order By: Relevance
“…48-0123). 33 Similar to previous studies, several excess diffraction peaks matched with Co 3 O 4 and La 2 O 3 (2θ = 24− 32°) are observed for chem-500 (sample 3), which demonstrated the difficulty to obtain pure LaCoO 3 phase at a lower temperature through the conventional method. 28,34 When the calcination temperature is raised to 700 °C (chem-700, sample 4), a pure perovskite phase of LaCoO 3 can be obtained.…”
Section: Resultssupporting
confidence: 86%
See 1 more Smart Citation
“…48-0123). 33 Similar to previous studies, several excess diffraction peaks matched with Co 3 O 4 and La 2 O 3 (2θ = 24− 32°) are observed for chem-500 (sample 3), which demonstrated the difficulty to obtain pure LaCoO 3 phase at a lower temperature through the conventional method. 28,34 When the calcination temperature is raised to 700 °C (chem-700, sample 4), a pure perovskite phase of LaCoO 3 can be obtained.…”
Section: Resultssupporting
confidence: 86%
“…The nitrogen adsorption-desorption isotherms (Figure 5) show the hysteresis loops at P/P0 = 0.8-0.9 corresponding to the gaps piled up by nanoparticles. 31,40 . The textural properties are shown in Table 3.…”
Section: Morphology Textural and Surface Properties Of Bio-lacoo3mentioning
confidence: 99%
“…It is reported that the more exposed surface Co 3+ in Co-based catalyst will be conducive to the enhancement of oxidation performance. 41,42 As listed in Table 3, the Co 3+ /Co 2+ molar ratio increases in the sequences Co 1 Mn 2 O δ < Co 1.5 Mn 1.5 O δ < Co 2 Mn 1 O δ . The order is opposite to that of Mn 4+ /Mn molar ratio, which may be caused by the electron transfer from Co to Mn atoms.…”
Section: ■ Results and Discussionmentioning
confidence: 95%
“…Co 2p XPS spectra (Figure b) are divided into Co 2p 3/2 and Co 2p 1/2 . The binding energies at 780.1 and 781.4 eV are assigned to Co 3+ and Co 2+ , respectively, while the peaks situated at 784.4, 789.8, and 804.2 eV belong to satellite peaks. The surface Co 3+ /Co 2+ can be calculated from its corresponding XPS integral areas, and the results are tabulated in Table S1.…”
Section: Results and Discussionmentioning
confidence: 99%